ICERI2018 Proceedings 2018
DOI: 10.21125/iceri.2018.2474
|View full text |Cite
|
Sign up to set email alerts
|

Hazards and Risks of Machine-Tools: An Experience in the Mechanical Technology and Vehicles Course

Abstract: Given the specificity of the Higher Professional Technical Courses it is important that the classes are oriented in order to promote a learning with a strong connection to the practice and its course. Following this principle, it was proposed to the students of the Mechanical Technology and Vehicles course of the School of Technology and Management of the Polytechnic Institute of Bragança (Portugal) that attended in 2017/2018 the course unit "Safety and Environment", the accomplishment of a practical work that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The proposed work was divided into three stages: 1) data collected by the students in the laboratories; 2) risk analysis (identification of hazards and consequent risks associated with the laboratory test/machine use and applicable legislation); 3) risk assessment (application of one of the methods studied in the theoretical part) and 4) preventive measures to be implemented in the situations concerned. Based on the analysis carried out, the students performed a written assignment and made their presentation to the class [5][6][7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed work was divided into three stages: 1) data collected by the students in the laboratories; 2) risk analysis (identification of hazards and consequent risks associated with the laboratory test/machine use and applicable legislation); 3) risk assessment (application of one of the methods studied in the theoretical part) and 4) preventive measures to be implemented in the situations concerned. Based on the analysis carried out, the students performed a written assignment and made their presentation to the class [5][6][7].…”
Section: Methodsmentioning
confidence: 99%
“…This approach was followed in the classes of the Safety and Environment CU of the Chemical and Biological Analysis (CBAnalysis) and Mechanical Technology and Vehicles (MTVehicles) CTeSPs of a higher education Institution in the North of Portugal, between the academic years 2016/17 and 2020/21. Based on the experiences carried out in the mentioned CU, Silva, Barros, and Ribeiro [5][6][7][8][9] concluded that when learning with a strong connection to practice is promoted, either in a laboratory or business context, there is evidence of a positive impact on student's motivation and learning. In this way, this paper aims to explain the approach applied in different academic years, reflecting on their advantages/disadvantages and possible perspectives of adaptation to the other component of the CU (Environment) or other courses.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative work between teachers from different areas and with different backgrounds, by promoting the debate on teaching and assessment practices, can boost the implementation of some more student-centred practices, with results considered favourable from a motivational and of learning point of view (e.g. [3], [4], [5], [6], [7], [8]). Continuing this dynamic of collaboration, the authors decided that it would be productive to extend it to the students themselves, as the exchange of knowledge between students could result in enriching learning for all involved.…”
Section: Introductionmentioning
confidence: 99%
“…Not only are students' agents of their own transformation, but also higher education institutions and teachers have a fundamental role in mediating these processes, facilitating and moderating learning contexts that are intended to be in constant evolution, transmutation, and transformation. It should be noted that the collaboration between teachers from different areas and with different backgrounds, who have been working as a team for some time [3], [4], [5], [6], [7], [8], [9], has contributed to the debate on teaching and assessment practices, leading to the implementation of some more student-centred practices, with results considered favourable from a motivational and learning point of view. For example, Silva, Barros, and Ribeiro [3], [4], [8], [9] concluded, based on their experiences with CTeSP students, that learning is promoted with a strong connection to practice, namely in the laboratory context, there is evidence of a positive impact on students learning.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the collaboration between teachers from different areas and with different backgrounds, who have been working as a team for some time [3], [4], [5], [6], [7], [8], [9], has contributed to the debate on teaching and assessment practices, leading to the implementation of some more student-centred practices, with results considered favourable from a motivational and learning point of view. For example, Silva, Barros, and Ribeiro [3], [4], [8], [9] concluded, based on their experiences with CTeSP students, that learning is promoted with a strong connection to practice, namely in the laboratory context, there is evidence of a positive impact on students learning. They also verified that the knowledge acquired in the performance of tasks can be useful for other course units.…”
Section: Introductionmentioning
confidence: 99%